Land-use transformation and carbon balance in Brazil’s biomes - Yulia S. Popova; Tatiana V. Komarova (RUDN Journal of Ecology and Life Safety)
The study reviews the types of land cover and analyzes the transformation of land use in Brazilian biomes over the past 30 years. Carbon balance data in connection with changes in land cover are analyzed. The total area of Brazil’s transformed lands has been counted more than 100 million hectares over the past 30 years. The biomes of Amazonia, Cerrado, Mata Atlantica and Caatinga have undergone the greatest changes. One of the main reasons for the transformation is the expansion of agricultural land through deforestation. Thus, the total proportion of the country’s lands subjected to deforestation is 72%. Anthropogenic land cover transformation affects the carbon content in the biomass. Carbon stocks in case of some biomes of Brazil are negative. The lowest rate in Caating is - 43.8 CO2 E/year. The analysis was based on open spatial, statistical data and international scientific publications. The aim of the research is to study land use transformation in some Brazilian biomes and carbon balance in their ecosystems.